Modeling of a Commercial BLDC Motor and Control Using GA- controller for a BLDC Propulsion Application for Hybrid Electric Vehicle - Pavan Kumar, KVNS; Prakash, S. (International Journal of Psychosocial Rehabilitation, 2019)
A wide amount of industries apply brushless DC (BLDC) motors for the advantage of having high effectiveness, speed, torque and low volume. The primary research concept is to give a development on whole representation of BLDC motor and also designing a optimal controller for controlling its position. Due to simple structure and easy implementation PSO controller is utilized for controlling many problems. Here in practical we didn’t get optimal performance by conventional practical PSO controller so for this purpose we propose a generic algorithm as a global optimizer for finding optimal PSO particles for reduction of torque ripples, setting current reducing control, current compensating of BLDC motor. So by utilizing generic algorithm a optimal design is performed on three phase brushless DC motor (TPBLDCM). Here the main objective of this optimal explore is to select the effectiveness of the motor and also the designing method is said as the maximum trouble which is depended on the value of a little particular motor considerations, has a relational study for improving motor and also designing a initial performance. Here the simulation resulting models of total electric propulsion may built analyzed by carrying standard driving schedule for performance indication of vehicle which is derived as a result of encouraging.